Depressive Symptoms and Associated Psychosocial Factors among Adolescent Survivors 30 Months after 2008 Wenchuan Earthquake: A Follow-Up Study - Shi, Xuliang; Yu, Nancy X.; Zhou, Ya; Geng, Fulei; Fan, Fang (Frontiers in Psychology, 2016)
Abstract Purpose: This study longitudinally investigated the changes of depressive symptoms among adolescent survivors over two years and a half after the 2008 Wenchuan earthquake in China, as well as the predictive effects of demographic characteristics, earthquake exposure, negative life events, social support and dispositional resilience on the risk of depressive symptoms at two time points after the earthquake. Methods: Participants were 1573 adolescent survivors (720 males and 853 females, mean age at initial survey =15 ± 1.26), whose depressive symptoms were assessed at 6 months (T6m) and 30 months (T30m) post-earthquake. Data on demographics, earthquake exposure and dispositional resilience were collected at T6m. Negative life events and social support were measured at T6m and 24 months (T24m) post-earthquake. Results: The prevalence rates of probable depression, 27.5% at T6m and 27.2% at T30m, maintained relatively stable over time. Female gender was related with higher risk of depressive symptoms at both T6m and T30m, while being only-child could only predict higher risk of depressive symptoms at T30m. Negative life events and social support at T6m, as well as earthquake exposure, were concurrently associated with increased risk of depressive symptoms at T6m, but not associated with the risk of depressive symptoms at T30m, while negative life events and social support at T24m could predict depressive symptoms at T30m, all of which suggested that these variables may have strong but short-term effect on adolescents’ depressive symptoms post-earthquake. Besides, dispositional resilience was evidenced as a relatively stable negative predictor for depressive symptoms. Conclusions: These findings could inform mental health professionals regarding how to screen adolescent survivors at high risk for depression, so as to provide them with timely and appropriate mental health services based on the identified risk and protective factors for depressive symptoms.